Treatment with specific and pan-plasma membrane calcium ATPase (PMCA) inhibitors reduces malaria parasite growth in vitro and in vivo - Puji B. S. Asih; Josephine E. Siregar; Farahana K. Dewayanti; Normalita E. Pravitasari; Ismail E. Rozi; Andita F. M. Rizki; Rifqi Risandi; Kevin N. Couper; Delvac Oceandy; Din Syafruddin (Malaria Journal, 2022)
Abstract Background Rapid emergence of Plasmodium resistance to anti-malarial drug mainstays has driven a continual effort to discover novel drugs that target different biochemical pathway (s) during infection. Plasma membrane Calcium + 2 ATPase (PMCA4), a novel plasma membrane protein that regulates Calcium levels in various cells, namely red blood cell (RBC), endothelial cell and platelets, represents a new biochemical pathway that may interfere with susceptibility to malaria and/or severe malaria. Methods This study identified several pharmacological inhibitors of PMCA4, namely ATA and Resveratrol, and tested for their anti-malarial activities in vitro and in vivo using the Plasmodium falciparum 3D7 strain, the Plasmodium berghei ANKA strain, and Plasmodium yoelii 17XL strain as model. Results In vitro propagation of P. falciparum 3D7 strain in the presence of a wide concentration range of the inhibitors revealed that the parasite growth was inhibited in a dose-dependent manner, with IC50s at 634 and 0.231 µM, respectively. Results The results confirmed that both compounds exhibit moderate to potent anti-malarial activities with the strongest parasite growth inhibition shown by resveratrol at 0.231 µM. In vivo models using P. berghei ANKA for experimental cerebral malaria and P. yoelii 17XL for the effect on parasite growth, showed that the highest dose of ATA, 30 mg/kg BW, increased survival of the mice. Likewise, resveratrol inhibited the parasite growth following 4 days intraperitoneal injection at the dose of 100 mg/kg BW. Conclusion The findings indicate that the PMCA4 of the human host may be a potential target for novel anti-malarials, either as single drug or in combination with the currently available effective anti-malarials.